The state of the art on social interactions in virtual project teams - Calçada Junior, Laurival Siqueira; Vils, Leonardo; Chaves, Marcírio (Revista de Administração da UFSM, 2024)
Purpose: This paper presents a better understanding of the state of the art of social interactions in virtual project teams based on comprehensive literature. Methodology: This literature review comprises 125 articles from 2017 to October 2023. Findings: We show that knowledge sharing, social identity, team cognition, psychological safety, and absorptive capacity are adopted to improve understanding of social interactions in virtual project teams. Practical implications: The conclusions can help managers understand the factors that drive effectiveness in project management and their main barriers. The identified factors represent the focus of the research in the literature. Originality: This study is original for integrating the themes of social interactions and virtual project teams and for the analysis at three levels: selected articles, most cited articles, and systematic reviews present in the sample. Knowledge sharing is emphasized as the only recurrent theme across all three levels of analysis and research agendas.